Local Knowledge of Coastal Women in Fisheries Resources Management (Study on Puger Coastal Women, Jember Regency) - Saputra, Aditya Eka; Indrianti, Deditiani Tri; Alkornia, Sylva (Indonesian Journal of Adult and Community Education, 2024)
The purpose of the research is to describe the local knowledge ofcoastal women in the management of fisheries resources (study oncoastal women of Puger, Jember Regency). Local knowledge ofcoastal women is analyzed through the theory of ecofeminism.Meanwhile, the management of fisheries resources carried out bywomen can be seen from community participation andcommunication skills. The type of research used is descriptive witha qualitative approach. Data collection techniques throughobservation, interviews, and documentation. Data analysistechniques used were data reduction, data presentation, andconclusion drawing. The results showed that coastal women's localknowledge is based on their experience from generation togeneration which will cause them to be able to dominateparticipation in fisheries resource management. The ability ofcoastal women in selling their catches is based on theircommunication skills. In the view of ecofeminism, the involvementof coastal women must be recognized in managing and protectingnature in addition to their needs